M3: an integrative framework for structure determination of molecular machines - Karaca, Ezgi; Bonvin, Alexandre M. J. J.; Carlomagno, Teresa (Nature methods, 2017)
We present a broadly applicable, user-friendly protocol that incorporates sparse and hybrid experimental data to calculate quasi-atomic-resolution structures of molecular machines. The protocol uses the HADDOCK framework, accounts for extensive structural rearrangements both at the domain and atomic levels and accepts input from all structural and biochemical experiments whose data can be translated into interatomic distances and/or molecular shapes.
Gesehen am 09.11.2018